On the Professional Development of English Teachers in Colombia and the Historical Interplay with Language Education Policies - Adriana González-Moncada (Asociación Colombiana de Profesores de Ingles, 2021)
The professional development of English teachers is a significant area in language teaching and learning, as well as in teacher education. On the one hand, at least in theory, professional development initiatives respond to the teachers' changing needs. On the other hand, it reflects the beliefs that different educational authorities and stakeholders have about English uses and education. In this self-study, I consider the professional development of English teachers in Colombia and its tight connection to the language education policies of the country. Following a chronological approach, I present the findings as landmarks that have contributed to my reflections and research around professional development and language education policies.  Discussing the findings, I show how the discourses and decisions about teachers' continuing learning represent certain views of language, second language acquisition, English language teaching and learning, and teachers as professionals. This self-study addresses some of the concepts that illuminate the discourses that have shaped English teachers' professional development. Focusing primarily on the development of the National Program of Bilingualism, I underscore the power of these concepts over the major decisions made at the local and school levels. In the analysis of the past and present of teachers' professional development in Colombia, I conclude on the necessity of maintaining critical scholarly work to contribute to the construction of local knowledge for future reflection.